Acute amiodarone toxicity causing respiratory failure - Kaya,Saltuk Bugra (2017)
Summary A 66-year-old male patient was referred to our clinic with severe pneumonia. Bronchoscopy was performed due to clinical worsening despite antibiotics and diuretic therapy, respiratory failure and radiographic progression. Because bacterial cultures of the bronchoalveolar lavage fluid were negative and after using amiodarone for almost one month, we eliminated amiodarone from his medication regimen due to suspicion of amiodarone toxicity. Accordingly, we also initiated systemic steroid therapy. Chest X-ray done after 72 hours showed a significant resolution of lung consolidations and the patient exhibited significant clinical improvement, with decline of his oxygen requirements.